2015
DOI: 10.4158/ep14197.cr
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Primaty Adrenal Leiopyosarcoma: A Complete Literature Review and Presentation of a Rare Adrenal Tumor

Abstract: Objective: Leiomyosarcomas are mesenchymal tumors that very rarely present as a primary adrenal malignancy. Methods: We present the complete clinical presentation, imaging, and anatomicopathologic features of a unique case of recurrent primary adrenal leiomyosarcoma (PAL) after initial surgery. This case is accompanied by an updated literature review. Results: A 63-year-old Hispanic female referred to our clinic 4 months after having right adrenalectomy. Eight months prior to this encounter, she started to not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(17 citation statements)
references
References 19 publications
(17 reference statements)
0
12
0
Order By: Relevance
“…A total of 3 cases out of 45 presented as an enlarging abdomen mass (32,65,66), 4 presented with dyspnoea or chest discomfort (32)(33)(34)67), 2 cases had fever at the time of diagnosis (33,56) and nausea (50,68). Five cases out of 45 presented with leg swelling (32,49,59,67,69) 1 with cold feet sensation (35) and 2 cases had skin varices at the time of diagnosis (67,69). One case presented with weight gain (32), 1 had back pain related with bone metastases (34), 1 had urinary track symptoms (70) and 3 were asymptomatic (71)(72)(73).…”
Section: Symptoms Diagnosismentioning
confidence: 99%
See 4 more Smart Citations
“…A total of 3 cases out of 45 presented as an enlarging abdomen mass (32,65,66), 4 presented with dyspnoea or chest discomfort (32)(33)(34)67), 2 cases had fever at the time of diagnosis (33,56) and nausea (50,68). Five cases out of 45 presented with leg swelling (32,49,59,67,69) 1 with cold feet sensation (35) and 2 cases had skin varices at the time of diagnosis (67,69). One case presented with weight gain (32), 1 had back pain related with bone metastases (34), 1 had urinary track symptoms (70) and 3 were asymptomatic (71)(72)(73).…”
Section: Symptoms Diagnosismentioning
confidence: 99%
“…Two cases described by Boman et al that presented positive EBER hybridization in the autopsy specimen, were found negative for EBV latent membrane protein 1 (LMP1) in the tumor cells (3). From the remaining literature 6 cases were tested negative for HIV infection (44,49,58,61,66,71). From these, one case was also tested for EBV in situ hybridization of the surgical specimen and was found negative (71) and another case was found negative for EBV LMP1 in the tumor cells (56).…”
Section: Risk Factorsmentioning
confidence: 99%
See 3 more Smart Citations